2013
DOI: 10.2298/mpns1302046v
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of asthma and chronic obstructive pulmonary disease in primary care patients

Abstract: A significant number of patients seen in the general practitioner's office were diagnosed with chronic obstructive pulmonary disease or asthma and half of them represent new cases. A substantial proportion of patients referred to a pulmonologist by primary care physicians have been misdiagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
7
1
1
Order By: Relevance
“…Mortality rate detected in our study was higher than the values previously reported in Serbia [14]. The death rate from COPD grew by 15% during the five-year period.…”
Section: Discussioncontrasting
confidence: 78%
“…Mortality rate detected in our study was higher than the values previously reported in Serbia [14]. The death rate from COPD grew by 15% during the five-year period.…”
Section: Discussioncontrasting
confidence: 78%
“…Prevalence of chronic bronchitis symptoms in Belgrade, Serbia was 21.6% 3 . Also, in the other study COPD diagnosis, confirmed by the pulmonologist, was in 21.9% of the patients and newly diagnosed COPD in 10.9% of the patients 4 .…”
Section: Introductionmentioning
confidence: 65%
“…The prevalence of COPD in the general population ranges from 0.2% to 18.3%. In Europe, it is estimated to range from 4% to 10%, 13 whereas the incidence of newly diagnosed cases of COPD in high-risk populations varies from 10.9% to 29.5%, 14 - 17 depending on the geographic location, the structure of the study population, and the scope of previous screening for COPD. The major reason for a late diagnosis of COPD is that the majority of patients with decreased FEV 1 do not complain of any respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%